Analysis of Renal Resistive Index As A Predictor of Acute Kidney Injury in Critical Care Patients - Denny Andrea; Nurul Machillah; Fadhilah Rahmi; Teuku Yasir; Muhsin Muhsin; Iskandar Zakaria; Maimun Syukri (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Acute kidney injury (AKI) is a common complication in critically ill patients and is associated with increased length of hospital stay. Early detection of renal dysfunction by measuring the renal resistive index (RRI) using Doppler ultrasound is a non-invasive parameter that reflects intrarenal vascular resistance and has the potential to predict AKI occurrence in critically ill patients. This study aims to compare RRI values between patients with and without AKI based on severity levels classification from AKIN criteria, and to establish the RRI value as a predictor of AKI occurrence in critically ill patients. This study was an analytical observational study with a prospective cohort design conducted on critically ill patients treated in the ICU of dr. Zainal Abidin Banda Aceh General Hospital from June to August 2025. Data were obtained through Doppler ultrasound RRI examination performed within the first 24 hours and medical record data during treatment. Data were analyzed using ANOVA and ROC curve analysis to determine the cut-off value of RRI as an AKI predictor. Out of the 60 critically ill patients who met inclusion criteria, 30 patients (50%) developed AKI during treatment. There were significant differences (p<0.0001) between RRI and AKI occurrence as well as AKI severity, for both the right and left kidneys. ROC curve analysis identified an RRI cut-off value of 0.7 for predicting AKI, with a Receiver Operating Characteristic Area Under the Curve (AUC) of 0.9628 and CI 95% : 0.9155 – 1.000, yielding a sensitivity and specificity of 90%. There are significant differences in RRI values between non-AKI patients and AKI patients at stages 1, 2, and 3. RRI value can be used as a predictor for AKI occurrence in critically ill patients. Keywords: Acute Kidney Injury, Critically Ill, Doppler Ultrasonography, Renal Resistive Index.